Scattering Analysis of Modulated Corrugations in a Conducting Circular Cylinder and Study of RCS Reduction - Lee, Sangsu; Jung, Kyung Young; Choo, Hosung; Park, Yong Bae (IEEE Transactions on Antennas and Propagation, 2019)
In this communication, an electromagnetic boundary-value problem of modulated transverse corrugations in an infinite conducting circular cylinder is rigorously solved based on the Fourier transform, eigenfunction expansion, and the mode matching method. Radar cross section (RCS) of the modulated transverse corrugations is represented in the series form. Computation is performed to analyze scattering characteristics while varying depth, width, and period of the corrugations and to investigate the excitation of surface waves and concomitant RCS reduction.
Keywords: Corrugated surfaces; Electromagnetic scattering; Electromagnetics; Mode matching method; Optical surface waves; Transverse corrugation; Mode matching method; radar cross section (RCS); surface waves; transverse corrugations